Modeling and simulation of a fixed bed gasification process for thermal treatment of municipal solid waste and agricultural residues - Oliveira, Matheus (2021)
This work aims to develop a numerical simulation model of the combined and integrated production process of combustion and gasification, for a synthesis gas production system (SYNGAS), fed with municipal solid waste (MSW), agricultural and forestry waste. For this purpose, the EMSO software (Environment for Modeling, Simulation, and Optimization) was used in the formulation of a fixed-bed gasifier with the co-current flow. The model is developed based on mathematical calculations of partial differential equations, being one-dimensional (1-D), and considers chemical kinetics, diffusivity, and heat and mass transfer phenomena. Its validation is based on data available in the literature (variables, initial and operational conditions). As a result, a simulation of a gasifier was obtained, capable of predicting the production of Syngas, having a good correlation with the published experimental results. The general data obtained were in agreement, with high consistency for the analysis of the pilot plant in the laboratory and semi-industrial scale for solid waste processing. However, detailing the behavior of the gasifier is essential to maximize the efficiency of the process. For that, the numerical simulation tested several operational parameters, such as air–fuel ratio and gasifier temperature for instance.